Trichofolliculoma in Paediatric Age Group Boy: A Rare Case Report Highlighting Dermoscopic and Histopathological Findings - TS Rajashekar; K Suresh (Journal of Clinical and Diagnostic Research)
Trichofolliculoma (TF) is a rare, benign skin appendage tumour derived from hair follicle structures, most frequently observed in adults and primarily affecting the head and neck regions. Its occurrence in the paediatric population, particularly on the scalp, is exceptionally uncommon and often overlooked, as it can clinically resemble more prevalent lesions such as dermoid cysts, epidermoid cysts, and pilar cysts. This case report presents a unique situation involving a nine-year-old boy with a solitary, asymptomatic, skin-coloured nodule on the scalp that had slowly increased in size since early childhood. Clinical evaluation revealed a central pore with a tuft of protruding hair, along with mild surrounding erythema and fine scaling. Dermoscopy showed a central white plug of hair, yellowish-white lobular areas, and visible dilated blood vessels, collectively pointing toward a follicular tumour. Complete surgical excision was performed, and histological analysis confirmed the diagnosis of TF, revealing a dilated central follicle giving rise to multiple smaller secondary follicles and keratin-filled cystic areas. This case underscores the importance of considering TF as a potential diagnosis in children presenting with longstanding scalp nodules, even when asymptomatic. Early dermoscopic assessment, followed by confirmatory histopathology, plays a vital role in accurate diagnosis and curative treatment, helping to prevent misdiagnosis and avoid unnecessary interventions. The rarity of this presentation highlights the need for clinical awareness and reinforces the diagnostic value of correlating clinical, dermoscopic, and histological findings in paediatric dermatology.